2023
DOI: 10.3390/bs13120987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Executive Functions among College Students in China: Exploring the Influence of Exercise Intensity and Duration

Ming Yu,
Xinyi Han,
Xiaomei Wang
et al.

Abstract: Background: This study investigates the effects of exercise intensity and duration on executive functions among college students in China. Method: Participants in this study were Chinese college students divided into four groups based on exercise duration and intensity. Each group engaged in physical exercise twice a week for six weeks. Group 1 performed low-intensity exercises for 10 min per session; Group 2 performed low-intensity exercises for 20 min per session; Group 3 performed high-intensity exercises f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…For example, a recent study reported that a single session of aerobic exercise increased BDNF serum levels [88]. Complementary to the above, PA interventions have been shown to improve EFs in university students [89]. However, that study did not find associations between ST, eating habits, sleep, and EFs.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a recent study reported that a single session of aerobic exercise increased BDNF serum levels [88]. Complementary to the above, PA interventions have been shown to improve EFs in university students [89]. However, that study did not find associations between ST, eating habits, sleep, and EFs.…”
Section: Discussionmentioning
confidence: 96%